Mast cells are at the interface between the external environment and the inner organism - Ribatti, Domenico (Frontiers in Medicine, 2024)
Mast cells localized at the level of the mucosal barrier in the skin, lung, and gastrointestinal tract, intervene in the modulation of the function of the epithelial cells and are involved in innate and adaptive defensive responses. In this context, mast cells intervene in the recognition and clearance of microbial pathogens. This mini-review article discusses the role of mast cells in these barrier systems.